Meningkatkan kinerja gardu distribusi SK76 Penyulang Sukasada dalam menangani overblast menggunakan simulasi perangkat lunak ETAP - I Putu Sutawinaya; Anak Agung Ngurah Made Narottama; I Gusti Ngurah Ade Pujana (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
Distribution transformer serves to transform electrical energy from the power source to the customer. In the transformation process there are power losses which of course can reduce the efficiency of the transformer. The relatively high loading on the transformer will cause an increase in power losses, so its efficiency will decrease. The Sukasada Feeder SK76 Distribution Substation with a transformer capacity of 100 kVA supplies 253 customers with an installed power of 273 kVA. Based on the measurements that have been made during the peak load time (WBP), the average percentage of the transformer loading is 99.57% with an efficiency of 98.02%. Referring to the Circular of the Directors of PT. PLN (Persero) No.: 0017.E/DIR/2014, then the transformer has been declared overload (overblast) because the load has exceeded 80%. Efforts that can be made to improve the performance of the transformer include: upgrading the capacity of the transformer, adding additional substations or through network reconfiguration. Based on the trials that have been carried out by the author through the simulation of the ETAP 16.0 software, several results were obtained. If an uprating is carried out with a transformer capacity of 160 kVA, the percentage of loading decreases to around 61.46% with efficiency increasing to about 98.77%. If additional substations are added with a capacity of 50 kVA as well as network reconfiguration by transferring some of the load to another Distribution Substation (SK63), the result is that the percentage of loading is reduced to around 63.17% and efficiency increases to about 98.46%. The simulation results that have been carried out show that this condition has met the provisions/regulations set by PT. PLN (Persero).